Secundum naturam: The Inheritance of Virtue in Ælred's Genealogy of the English Kings - Mayeski, Marie Anne (Cistercian studies quarterly, 2002)
Discusses the concept of inheritance of virtue in the genealogy of English kings. Narratives of royal ancestry; Theological theme of inherited virtue; Theoretical significance to Cistercian studies.